Bridge Over Troubled Water: Shared Understanding Bridges Individual and Collective Resources in Developing Team Resilience in Professional Football - Grinde, Ole Erik (Frontiers in Sports and Active Living, 2021)
This study explored how coaches facilitate coordinated activities through shared understanding in the processes of team resilience development. Constructs of shared information that underpin synchronised actions and behaviour in a team are investigated through individual experiences with a dialogic “we” perspective of appropriating and handling challenging situations. Interactional key elements underpin coordinated task actions within the team. Experiences of both players and coaches are investigated through semi-structured interviews and complementary texts such as an observation log and coach-meeting reports, originating as part of an action research process in the team environment. The interaction model is developed in the exploratory journey during the season with the team. The model suggests key strategic elements that help to bridge shared appropriation of information to strengthen role interactions between team members handling challenging situations. Coaching practise, which connects the interaction model to different team resources of coordinating activities in the development process, still needs to be explored from different contextual perspectives and environments, within the development of team resilience.